KARAKTERISTIK PEWARNA ALAMI PADA EKSTRAK Sargassum polycystum DENGAN KONSENTRASI PELARUT ETANOL DAN LAMA MASERASI YANG BERBEDA - Indra Pratista, I Made; Suhendra, Lutfi; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
Sargassum polycystum is one type of brown seaweed (Phaeopychae) which contains various pigment content such as beta carotene, chlorophyll a and b, and fucoxanthin. The pigment content of Sargassum has many potential benefits in both health and industry. The purpose of this study was to determine the effect of ethanol solvent concentration and maceration time on the natural dye characteristics of Sargassum polycystum extract, to determine the best solvent concentration and maceration duration in producing natural dyes from Sargassum polycystum extract. The experiments in this study used Factorial Randomized Block Design (RAK) with two factors. The first factor was the concentration of ethanol solvent consisting of 3 levels, ie 75%, 85%, and 95%. The second factor is the duration of maceration consisting of three levels, ie 12 hours, 24 hours and 36 hours. The variables analyzed were rendement, chlorophyll a, b and total chlorophyll and color intensity (L *, a *, b *). The results showed that the concentration of ethanol solvent and maceration time had significant effect on all the variables tested. The interaction between ethanol concentration and maceration durations had significantly effect on chlorophyll content of Sargassum polycystum extract, significantly affecting the color intensity of L *, and had no significant effect on color intensity a * and b *. The treatment of 95% ethanol solvent concentration and 36 hours of maceration time produced the best characteristic with yield of extract 2,21%, chlorophyll a 93,4 ppm, chlorophyll content b 206,9 ppm, total chlorophyll content 300,7 ppm, and color intensity (L *) 4.41, (a *) -3.91, (b *) 38.06. Key words: Sargassum polycystum, solvent concentration, maceration time, natural dye.